Shakespeare, the Renaissance and empire. Volume 1, geography and language - Hart, Jonathan Locke, 1956- (New York, NY : Routledge, 2021)
"Shakespeare, the Renaissance and Empire presents Shakespeare as both a local and global writer, investigating Shakespeare's trans-cultural writing through the interrelations and interactions of binaries including theory and practice, past and present, aesthetics and ethics, freedom and tyranny, republic and empire, empires and colonies, poetry and history, rhetoric and poetics, England and America, and England and Asia. The book breaks away from traditional western-centric analysis to present a universal Shakespeare, exposing readers to the relevance and significance of Shakespeare within their local contexts and cultures. This text aims to present a global Shakespeare, utilizing a dual perspective or dialectical presentation, mainly centred on questions of (1) how Shakespeare can be viewed as both an English writer and a world writer; (2) how language operates across genres and kinds of discourse; and (3) how Shakespeare helps to articulate a poetics of both texts (literature) and contexts (cultures). The book's originality lies in its articulation of the importance and value of Shakespeare in the emerging landscape of global culture"--
Geography, Asia and otherness -- Rhetoric and English history -- The language of history, governance and of civil war -- The words of kingship and war -- Political rhetoric in Rome -- Translation and history -- Empire, Ireland and the New World -- Hamlet on film in Asia.
OCLC-licensed vendor bibliographic record.
Keywords: Shakespeare, William, -- 1564-1616 -- Criticism and interpretation; Shakespeare, William, -- 1564-1616 -- Language; LITERARY CRITICISM / General; LITERARY CRITICISM / Shakespeare